Electric Field Distributions of the Fast and Slow Modes Propagated in the Open Rod SiCWaveguide - Nickelson, L.; Gric, T.; Asmontas, S.; Martavicius, R. (Elektronika ir Elektrotechnika, 2009)
Here we present the electrodynamical analysis of the ceramic circular rod silicon carbide (SiC) waveguide with the radius R = 2.5 mm at the temperature 1800° C. We present dispersion characteristics of the SiC waveguide in the frequency range 1−100GHz. We show the losses of two slow and one fast waveguide modes. We give here the electric field distributions of the slow and fast modes propagated in the investigated waveguide. We present a table with magnitudes of the electric and magnetic field components in the fixed point of the SiC waveguide cross-section. Ill. 5, bibl. 9 (in English; summaries in English, Russian and Lithuanian).